Minimum wage and collective bargaining shocks: A narrative database for advanced economies - António Afonso; Jo\~ao Tovar Jalles; Zoe Venter (IZA Journal of Labor Policy, 2023)
This paper presents and describes a new database of major minimum wage and collective bargaining (CB) shocks covering 26 advanced economies over the period 1970-2020. The main advantage of this dataset is the precise identification of the nature and date of major shocks, which is valuable in many empirical applications. Based on the dataset, we observe that major changes in minimum wages have been more frequent than in CB in the last decades, and the majority of these were implemented during the 1980s and 1990s. In our empirical application, we find that minimum wage policy reductions have a medium-run positive impact on labor productivity and they lead to a fall in the unemployment rate. CB policy liberalizations do not seem to affect either productivity or capital formation, but they have a clear medium-term effect on the labor market. Moreover, CB policy liberalizations are characterized by a greater sensitivity to the prevailing business cycle conditions at the time of the shock (vis-à-vis minimum wage reforms).
Keywords: C22; E24; J31; J52; 330; labor market policies; minimum wage; collective bargaining; labor productivity; growth; local projection